Uncovering the multifaceted properties of 6-pentyl-alpha-pyrone for control of plant pathogens - Mendoza-Mendoza, Artemio; Esquivel-Naranjo, Edgardo Ulises; Soth, Sereyboth; Whelan, Helen; Alizadeh, Hossein; Echaide-Aquino, Jesus Francisco; Kandula, Diwakar; Hampton, John G. (Frontiers in Plant Science, 2024)
Some volatile organic compounds (VOCs) produced by microorganisms have the ability to inhibit the growth and development of plant pathogens, induce the activation of plant defenses, and promote plant growth. Among them, 6-pentyl-alpha-pyrone (6-PP), a ketone produced by Trichoderma fungi, has emerged as a focal point of interest. 6-PP has been isolated and characterized from thirteen Trichoderma species and is the main VOC produced, often accounting for >50% of the total VOCs emitted. This review examines abiotic and biotic interactions regulating the production of 6-PP by Trichoderma, and the known effects of 6-PP on plant pathogens through direct and indirect mechanisms including induced systemic resistance. While there are many reports of 6-PP activity against plant pathogens, the vast majority have been from laboratory studies involving only 6-PP and the pathogen, rather than glasshouse or field studies including a host plant in the system. Biopesticides based on 6-PP may well provide an eco-friendly, sustainable management tool for future agricultural production. However, before this can happen, challenges including demonstrating disease control efficacy in the field, developing efficient delivery systems, and determining cost-effective application rates must be overcome before 6-PP’s potential for pathogen control can be turned into reality.